SOME ASPECTS OF THE INTEGRATION OF PEER-ASSESSMENT IN EFL WRITING CLASSROOM (CASE OF GEORGIA) - Diakonidze, Inga (International Journal of Innovative Technologies in Social Science, 2022)
Writing skills are considered to be the most challenging skills for a second language learner to master. Large number of studies have been carried out to address this issue. The researchers emphasise the vital role of adequate pedagogical approach, fair assessment, and constructive feedback in teaching writing. The main focus of this study is peer assessment, as one of the most effective techniques for developing writing skills by giving feedbacks and assessments. However, this technique, similar to any other methodological tools, can encounter the problems. This research highlights some of the major problems encountered in the peer assessment process and suggests recommendations for their solution. Empirical data of this study are collected from self-reflective classroom practice of peer-assessment. Quantitative analysis is performed on the points assigned by the peers and by the professor by using t-test. Qualitative analysis is carried out based on class observation and thematic analysis of the feedbacks provided by the participants. The results of the research show that the most significant factors that hinder successful implementation of peer assessment in EFL classroom in Georgia, are the social factor of friendship and the lack of oral interaction between the reviewer groups and the reviewees. Respectively, adoption of the two-fold model of peer-assessment that includes: 1. Written format of peer-assessment with final points assigned by the professor and 2. Oral interaction between the assessor(s) and assessed students, makes the peerassessment one of the most effective techniques for developing writing skills in EFL classes in Georgia.